2019
DOI: 10.1093/infdis/jiz272
|View full text |Cite
|
Sign up to set email alerts
|

A New Sequence Type of Neisseria meningitidis Serogroup C Associated With a 2016 Meningitis Outbreak in Mali

Abstract: In 2016, Mali reported a bacterial meningitis outbreak consisting of 39 suspected cases between epidemiologic weeks 9 and 17 with 15% case fatality ratio in the health district of Ouéléssebougou, 80 kilometers from the capital Bamako. Cerebrospinal fluid specimens from 29 cases were tested by culture and real-time polymerase chain reaction; 22 (76%) were positive for bacterial meningitis pathogens, 16 (73%) of which were Neisseria meningitidis (Nm). Of the Nm-positive specimens, 14 (88%) were N meningitidis se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…New STs may arise by horizontal gene transfer between circulating N . meningitidis strains and recombination events [ 37 ]. It is possible that clonal group ST-9493 is associated with the ST-41/44 cc or represents a new cc; however, additional genome analysis is required to more accurately reveal relationships among the strains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…New STs may arise by horizontal gene transfer between circulating N . meningitidis strains and recombination events [ 37 ]. It is possible that clonal group ST-9493 is associated with the ST-41/44 cc or represents a new cc; however, additional genome analysis is required to more accurately reveal relationships among the strains.…”
Section: Discussionmentioning
confidence: 99%
“…ST-9493 was identified in isolates collected from patients in an outbreak of IMD in Colombia, related to ST-41/44 cc [12], and from patients in different regions of the country, demonstrating the local expansion of this ST. Several studies have shown the emergence of new STs of N. meningitidis serogroup B are associated with outbreaks or endemic disease, and it may be considered as a new meningococcal cc [34][35][36]. New STs may arise by horizontal gene transfer between circulating N. meningitidis strains and recombination events [37]. It is possible that clonal group ST-9493 is associated with the ST-41/44 cc or represents a new cc; however, additional genome analysis is required to more accurately reveal relationships among the strains.…”
Section: Plos Onementioning
confidence: 99%
“…CC10217 is an emerging invasive CC that has already caused numerous outbreaks in the meningitis belt [5,6]. In our study, we identified carriage isolates belonging to this CC from three STs, two of which have been the cause of a recent outbreaks in Burkina Faso and in nearby countries such as Mali (ST-12446) [48], Niger and Nigeria (ST-10217) [6,49]. Our phylogenetic analysis revealed that the carriage and invasive isolates were genetically distinct; while carriage and invasive isolates belonging to the same ST were more closely related than to the other STs, they did not cluster together.…”
Section: Discussionmentioning
confidence: 99%
“…Outbreaks at subdistrict level and in hard-to-reach areas may therefore have been missed, as well as small outbreaks not meeting the standard regional definition. This was likely the case of a reported outbreak in Mali, in 2017 [33], which was not included here as it did not cross the epidemic threshold as per ES data. Of note, the definition of outbreaks in the meningitis belt is derived from historical NmA epidemics and calculation of weekly attack rates at the district level.…”
Section: Discussionmentioning
confidence: 99%